Syntheses, emission properties and intramolecular ligand exchange of zinc complexes with ligands belonging to the tmpa family - Beitat, Alexander; Foxon, Simon P.; Brombach, Christoph-Cornelius; Hausmann, Heike; Heinemann, Frank Wilhelm; Hampel, Frank; Monkowius, Uwe; Hirtenlehner, Christa; Knoer, Guenther; Schindler, Siegfried (Dalton Transactions, 2011)
The zinc complexes [(L1)(2)Zn(MeOH)(2)](OTf)(2), [(L1)ZnCl2], [(L-2)ZnCl2], [(L2)Zn(OTf)(H2O)]OTf and [(Me-bispic)ZnCl2] of the ligands N-[(2-pyridyl)methyl]-2,2'-dipyridylamine (L1), N-[bis(2-pyridyl)methyl]-2-pyridylamine (L2) and N-methyl-[bis(2-pyridyl) methyl]amine (Me-bispic) were synthesised and characterised. The first copper(I) complexes of the ligands L1 and L2 were also synthesised and structurally characterised. [(L1)ZnCl2] showed unexpected fluxional behaviour in solution and revealed an interesting intramolecular ligand exchange mechanism in the coordination sphere of the zinc ion. Furthermore, strong blue emission was observed under UV-light excitation.